How to deal with an "essentially contested concept" on the field? Sampling social innovations through the Delphi method - Callorda Fossati, Ela; Degavre, Florence; Nyssens, Marthe (European public & social innovation review, 2017)
How to select cases in social innovation research? Sampling units of analysis is indeed a challenging methodological question since social innovation theory is controversial and fragmented. In the absence of any database and given the limits of conventional techniques, sampling is only possible through participative methods that make sense of opposing perceptions and contestedness. This article presents the Delphi method and its related principles of expertise, iterative consultation and consensus forming and shows how it served to identify a pool of cases of social innovation, sort them out and finally establish a sample of social innovations in a partnership research on innovative practices in domiciliary eldercare.